Status, Ecology and Management of Scaled Quail in West Texas - Dale Rollins (National Quail Symposium Proceedings, 2017)
Scaled quail (Callipepla squamata), more commonly referred to as "blue" quail, have always been viewed as a secondary species among Texas quail hunters and managers, who generally prefer to hunt northern bobwhites (Colinus virginianus). Scaled quail and bobwhites are sympatric over much of west Texas, and the 2 species share several habitat characteristics (e.g., similar loafing coverts). In areas where the 2 species are sympatric, they have essentially the same diets. However, scaled quail tend to prefer more open habitats, i.e., less and lower herbaceous cover, than bobwhites. Scaled quail populations have declined precipitously since 1988 across virtually all of their Texas range. Radio-marked scaled quail apparently had higher survival rates than sympatric bobwhites from February to July, 1995 at a study site in Irion County, Texas. Historically, scaled quail do not seem to decline as quickly as bobwhites in dry years, but neither do they increase quite as dramatically as bobwhites during wet years. The effects of common management practices like brush control, supplemental feeding, and predator control have not been investigated adequately for scaled quail. Additional studies conducted with radio telemetry will undoubtedly cause us to reconsider the current paradigms of scaled quail management, as it has recently done with bobwhites.